Analisis Pengaruh Aplikasi Game Online Mobile Legend Di Kalangan Muda - Catherine.S.Lorentz Sitorus; Devi Patricia Hutagalung; Yuliana Sari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Currently we see how the development of mobile phones has greatly influenced games or video games. Now with Android-equipped phones that can load more data stored on the phone,